Sample attrition in the Canadian Survey of Labor and Income Dynamics - Brahim Boudarbat; Lee Grenon (Institute for the Study of Labor (IZA), 2013)
This paper provides an analysis of the effects of attrition and non-response on employment and wages using the Canadian Survey of Labour and Income Dynamics. We consider a structural model composed of three freely correlated equations for non-attrition/response, employment and wages. The model is estimated using microdata from 22,990 individuals who provided sufficient information in the first wave of the 1996-2001 panel. The main findings of the paper are that attrition is not random. Attritors and non-respondents likely are less attached to employment and come from low-income population. The correlation between non-attrition and employment is positive and statistically significant, though small. Also, wage estimates are biased upwards. Observed wages are on average higher than wages that would be observed if all the individuals initially selected in the panel remained in the sample.
Keywords: J21; J31; C33; 330; panel data; attrition; selection; SLID; Canada